PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PT. NOV PROFAB DI KOTA BATAM - Bella Kinanti; Jontro Simanjuntak (SCIENTIA JOURNAL, 2022)
The objectives of this research are to: (1) determine the impact of organizational culture on employee worksatisfaction; and (2) determine the impact of organizational culture on employee job satisfaction. assess theimpact of the workplace on employee job satisfaction. (3) assess the impact of employee motivation on worksatisfaction (4) Determine how company culture, work environment, and motivation affect employee jobsatisfaction.This is a quantitative study with a causal research design. The Slovin formula was used to calculatethe sample size, yielding a sample size of 183 persons.In this study, the hypothesis test is a multiple linearregression test.Given the significance value of 0.031<0.05 obtained from the data analysis, it can be inferredthat organizational culture has a considerable impacst on employees jobs satiisfaction. The significance valueof the environmental culture variable was 0.000< 0.05, indicating that environmental culture hat a significanceeffect on employee job satisfaction, while the motivational variable had a significance value of 0.000< 0.05,indicating that motivation had a significant effect on employee job satisfaction. With a significant value of0.000< 0.05, it can be inferred that organizational culture, work environment, and motivation all influence PT.Nov Profab's job satisfaction in Batam City